ECOSYSTEM APPROACH TO ENTREPRENEURSHIP IN THE CONTEXT OF DIGITALIZATION AS AN INNOVATIVE TOOL FOR MANAGING COMPETITIVENESS - DUBNITSKII, Volodymyr; PAVLOVA, Valentyna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article explores the features of the ecosystem approach to entrepreneurship as an innovative tool for managing competitiveness in the context of digitalization. Special attention is paid to the distinctive features of the formation and functioning of digital entrepreneurial ecosystems, their structural components, and their role in transforming traditional business models. It is substantiated that digital ecosystems contribute to the creation of new sources of competitive advantages through the integration of digital technologies, the development of strategic partnerships, and the enhancement of customer orientation. The research highlights the key directions for the implementation of digital ecosystems into the practice of strategic management. In particular, it emphasizes the importance of data-driven decision-making, platform-based business models, and the involvement of multiple stakeholders in co-creating value. The article also proposes approaches to assessing the impact of digital ecosystems on the competitiveness of enterprises, including performance metrics related to innovation capacity, adaptability, operational efficiency, and customer satisfaction. The findings suggest that the use of digital entrepreneurial ecosystems enables enterprises to enhance their flexibility, adaptability, and innovativeness, which are critically important in today’s dynamic and uncertain business environment.  The study concludes that the integration of digital ecosystems into enterprise strategy is not only a response to technological change but also a proactive step towards sustainable competitive development. These ecosystems foster the emergence of new forms of value creation and exchange, reshape industry boundaries, and stimulate continuous innovation. As a result, they become a vital element of modern competitive strategies, particularly for enterprises operating in highly volatile and competitive markets. The proposed conceptual framework provides practical insights for business leaders and policymakers on how to leverage digital ecosystems to strengthen enterprise competitiveness in the digital age.
Keywords: ecosystem approach; digitalization; digital entrepreneurial ecosystems; digital technologies; competitiveness; competitive advantages; enterprise competitiveness management